Factors associated with quality of life among family caregivers of terminally ill cancer patients. Issue 2 (7th July 2015) - Choi, Youn Seon; Hwang, Sun Wook; Hwang, In Cheol; Lee, Yong Ju; Kim, Young Sung; Kim, Hyo Min; Youn, Chang Ho; Ahn, Hong Yup; Koh, Su‐Jin
Abstract: Objective: Limited research has examined the quality of life (QOL) and its correlates among family caregivers (FCs) during the final stage of terminal cancer. The purpose of this study was to investigate the determinants of overall QOL and its subdomains among Korean FCs at the very end of life. Methods: For this cross‐sectional study, we enrolled 299 FCs of terminal cancer patients from seven palliative care units. To assess FCs' QOL and its predictors, we used the Caregiver Quality Of Life Index‐Cancer, which contains four domains. Possible determinants of caregiver QOL were categorized into patient, caregiver, and environmental factors. A multiple regression model was used to identify factors associated with FCs' QOL. Results: Variance in each Caregiver Quality Of Life Index‐Cancer domain was explained by different factors. FCs of younger patient felt more burden but were more likely to adapt positively. Emotional distress of FCs was strongly associated with total QOL, burdensomeness, and disruptiveness. Positive adaptation was related to more visits for care, FCs' religiousness, more social support, and satisfactory perceived quality of care. Financial concerns were more likely in married FCs, FCs with less social support, or low incomes. Conclusion: Emotional distress of FCs was the most important factor determining the overall and negative aspects of FCs' QOL, whereas various environmental factors were associated with positive coping. Appropriate support programs directed at these factors are needed to maintain and improve FCs' QOL. Copyright © 2015 John Wiley & Sons, Ltd.